2015
DOI: 10.21608/jssae.2015.43894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Manures Application on N Mineralization at Different Egyptian Soils.

Abstract: Organic manure is one of the sources of nitrogen in the soil. Nitrogen mineralization depends on application method, source of organic manure, microbial activity, aeration and moisture. The objective of this study was to investigate the rate of nitrogen mineralization as affected by different sources of organic manures (compost, chicken manures, and town refuse) which mixed with clay and sandy soils at the rate of 10 and 20 t fed-1 at different incubation periods. The experiment was carried out in laboratory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…It's called an interactive part of the soil organic component that is mineralized within a couple weeks or months under suitable conditions. The results matched with El-Ghamry et al (2015) and Zhao et al (2019). The organic forms of nitrogen that is present in a form of macromolecules gets slow release to a non-organic form, these plants were higher in soils amendments with compost rice straw alone or in addition to mineral fertilizers.…”
Section: Resultssupporting
confidence: 69%
“…It's called an interactive part of the soil organic component that is mineralized within a couple weeks or months under suitable conditions. The results matched with El-Ghamry et al (2015) and Zhao et al (2019). The organic forms of nitrogen that is present in a form of macromolecules gets slow release to a non-organic form, these plants were higher in soils amendments with compost rice straw alone or in addition to mineral fertilizers.…”
Section: Resultssupporting
confidence: 69%
“…At the Hawassa Zuria and Wondo Genet locations, at 42 days of incubation, the effects of the six Azolla biomass biofertilizer treatments on the ammonium content were as follows: control (0.66 mg kg-1, 0.88 mg kg -1 ), < 15 g kg -1 (3.44 mg kg -1 , 4.61 mg kg -1 ), < 30 g kg-1 (16.85 mg kg -1 , 21.35 mg kg -1 ), and < 45 g kg -1 (20.27 mg kg -1 , 24.58 mg kg -1 ) (Tables 1 and 2). The authors reported similar findings for other soil types, showing that organic fertilizers affected the ammonification of organic nitrogen during different incubation periods (El-Ghamry et al, 2015).…”
Section: Ammonium Nitrogen (Nh 4 + -N) Release Affected By Azolla Pin...supporting
confidence: 59%
“…Farm residues as well as the integrated processing and management of soil through composting (Xi, et al, 2005 andEl-Ghamry, et al, 2015) can importantly soil properties. Determining quality standards for organic farming can be a difficult task because of the heterogeneity of aggregated by-products.…”
Section: Introductionmentioning
confidence: 99%